2019
DOI: 10.3766/jaaa.17139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduced Audibility on Mini-Mental State Examination Scores

Abstract: The interaction of audition and cognition has been of interest to researchers and clinicians, especially as the prevalence of hearing loss and cognitive decline increases with advancing age. Cognitive screening tests are commonly used to assess cognitive status in individuals reporting changes in memory or function or to monitor cognitive status over time. These assessments are administered verbally, so performance may be adversely affected by hearing loss. Previous research on the impact of reduced audibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Several caveats regarding the reported findings should be noted: First, a relatively small number of participants was tested in the present study. However, the observation of a significant effect of simulated HL on cognitive-test performance echoes results from previous impairment-simulation studies investigating other cognitive tests using smaller and larger sample sizes [17,24,26,[28][29][30]. Second, only the effect of simulated HL on immediate verbal recall after a single presentation of the word list was assessed; delayed recall and recognition, which are also part of the revised version of the HLVT [31] and often used as independent or complementary indicators for changes in memory functions, were not explored.…”
Section: Discussionsupporting
confidence: 79%
“…Several caveats regarding the reported findings should be noted: First, a relatively small number of participants was tested in the present study. However, the observation of a significant effect of simulated HL on cognitive-test performance echoes results from previous impairment-simulation studies investigating other cognitive tests using smaller and larger sample sizes [17,24,26,[28][29][30]. Second, only the effect of simulated HL on immediate verbal recall after a single presentation of the word list was assessed; delayed recall and recognition, which are also part of the revised version of the HLVT [31] and often used as independent or complementary indicators for changes in memory functions, were not explored.…”
Section: Discussionsupporting
confidence: 79%
“…That is, people with better thresholds perceived sound at a greater SNR than people with worse thresholds. Gaete and colleagues 11 similarly reported reduced audibility negatively impacts scores on the Mini Mental State Examination, even in cognitively intact people.…”
Section: Hearing and Listening And Sensorineural Hearing Lossmentioning
confidence: 96%
“…In line with that Gaeta found that the performance in the MMSE was comparable in 30 elderly hearing impaired with a mean age of 69.4 and 30 younger adults aged 24.2 when a hearing loss was simulated. 56 Also, Verhaegen undermined these findings in a verbal recall task. 61 Augmentation by hearing aid use can reverse the bad performance in hearing-impaired subjects as shown by Jorgensen, Gaeta, Wong and MacDonald.…”
Section: Cognitive Testing In Subjects With Hearing Lossmentioning
confidence: 99%
“…52,53 The majority of currently used neurocognitive test batteries are based on oral instructions and include subtests relying on auditory functions which rise the bias of false positive results in multiple ways, especially in subjects with a lower educational background. [54][55][56][57] In the most frequently used neurocognitive screening batteries, the MMSE and the MoCA (Montreal Cognitive Assessment), 7 versus 10 out of 30 points depend on auditory presented stimuli, respectively. 47,48,58,59 This is also true for the DemTect, which is highly sensitive to (mild cognitive impairment) MCI detection and quite popular in Germany.…”
Section: Cognitive Testing In Subjects With Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation